An Overview of Fisheries and Aquaculture in the Philippines - TAHİLUDDİN, Albaris; TERZİ, Ertuğrul (Journal of Anatolian Environmental and Animal Sciences, 2021)
The Philippines is one of the significant contributors to world fisheries. In 2018, the total production from three sectors, e.g., aquaculture, municipal, and commercial fisheries, was about 4.36 million MT. With this, the Philippines ranked 13th as the top fish-producing country and placed 4th as the major seaweed producer worldwide. The total export earnings of the country from the fisheries sector was US$1.6 billion. The Philippine fisheries sector is an essential contributor to the national economy, providing income from foreign exchange and livelihood sources to almost 2 million Filipino fisherfolks. This review aimed to provide an overview of fisheries and aquaculture in the Philippines.
Keywords: 2. Zero hunger; 11. Sustainability; 8. Economic growth; 14. Life underwater; 12. Responsible consumption